THE DIGITAL REALITY FROM THE PERSPECTIVE OF COMMUNICATION PROCESSES AND EXISTENSE OF HUMAN - Ekaterina Viktorovna Lazinina (Sovremennye Issledovaniâ Socialʹnyh Problem, 2019)
Purpose. The article deals with the existence of digital area and term of digital reality in the paradigm of human existential space. It’s analyzing the terminological apparatus from the perspective of modern cybersystems and digital technologies. The author analyzes the processes of transformation of modern society and the formation of the digital society platform, analyzes changing of communication’s quality between its subjects. The obvious fact is the formation of a new cultural space within the framework of emergent digital reality, which requires philosophical understanding.